Two successful natural pregnancies in a patient with severe uterine prolapse: A case report - De Vita D; Giordano S (United Kingdom, 2025)
Introduction
Uterine prolapse is a common gynecologic condition that is rare during or before pregnancy. We report an exceptional case of two pregnancies in a totally prolapsed uterus.
Case presentation
A 36-year-old Caucasian woman with a history of uterine prolapse presented with pregnancy. A vaginal pessary was applied to keep her uterus inside the pelvis after manual reposition. The pessary was removed at the 24th week. The gravid uterus persisted in the abdominal cavity because of its increased volume.
Conclusion
Our case shows that pregnancy during uterine prolapse is possible and that careful assessment is required to prevent complications during delivery. According to our experience, an elective caesarean section near term could be the safest mode of delivery.